On groups with the minimal condition for non-invariant decomposable abelian subgroups - Lyman, F.N.; Drushlyak, M.G. (Algebra and Discrete Mathematics, 2006)
The infinite groups, in which there is no any infinite descending chain of non-invariant decomposable abelian subgroups (md-groups) are studied. Infinite groups with the minimal condition for non-invariant abelian subgroups, infinite groups with the condition of normality for all decomposable abelian subgroups and others belong to the class of md-groups. The complete description of infinite locally finite and locally soluble non-periodic md-groups is given, the connection of the class of md-groups with other classes of groups are investigated.